Biomarkers of chronic exposure to heavy metals in informal workers on the Colombian Caribbean coast. (2022)
Chronic exposure to heavy metals (HM) is a major source of disease throughout the world. Lead (Pb), cadmium (Cd) and mercury (Hg) are the heavy metals most frequently reported with occupational exposure and, consequently, their toxicity is associated with various chronic diseases. About half of the active population in Latin American countries works in informal jobs (I would define informal), which causes concern because these types of workers are associated with high health risks, even at low doses of chronic exposure to Pb, Cd, and Hg. Despite this concern, only a few reports address this problem in Latin America and the Caribbean. The objective of this research was to associate the concentrations of Cd, Pb and Hg to physiological and anthropometric variables of informal workers: Mechanics, welders, battery recyclers, garbage recyclers, from Cartagena city, as well as a group of miners from San Martin de Loba, Colombia. Whole blood levels of Cd, Pb, and mercury were measured for population groups according to the risk associated with their occupation. Heavy metals were determined using direct thermal discharge atomic absorption spectrometry for mercury and graphite furnace atomic absorption spectrometry for Cd and Pb. Mechanics, welding and recyclers workers were of a median age of 45 years (interquartile range (IQR), 33-53). The median blood Pb level (BLL) was 2 μg/dL (IQR, 0.76–6.22), and the median blood Cd level (BCL) was 1.22 μg/L (IQR, 0.33–2.01). It was found that 33% of high-exposure jobs had BLL > 5 μg/dL (n=57), while in 'control' workers it was 15.3% (n=9). The highest BLLs were obtained from battery recyclers (82.1%; n=23), followed by mechanics (37.3%, n=22). In the age-adjusted logistic regression model, time at work, smoking, and elevated BCL and BLL increased as much as 3.2-fold (95% CI, 1.1–9.7) in mechanics and 29.6-fold (95% CI, 7.2–145.6) in battery recyclers. This study found negative health impact in Cartagena Colombian workers with greater chronic exposure to Pb. A logistic regression to assess the effect of artisanal and small-scale gold mining (ASGM) on health outcomes on the mining population using univariate and bivariate statistical analyzes was performed for all variables. The enrolled volunteers (n = 124) were between the ages of 20 and 84 (84% miners and 79% men). No changes were found in (ASGM) workers, systolic blood pressure, diastolic blood pressure, and heart rate in crude and adjusted statistical analyses. ASGM miners had an 8.91 (95% confidence interval, 1.55–95.70)-fold increased risk of having these neurotoxic changes. Total blood mercury (T-Hg) concentrations in all participants ranged from 0.6 to 82.5 with a median of 6.0 μg/L. Miners have higher T-Hg concentrations than non-miners (p -value = 0.011). Normal and abnormal respiratory spirometry patterns showed significant differences with the physical role and physical function of the quality of life scales (p-value was 0.012 and 0.004, respectively). Spirometry testing was performed on 87 male miners, with 25% of these miners reporting abnormalities. Of these, 73% presented a restrictive spirometry and 27% an obstructive spirometry pattern. The ASGM population exhibited higher blood Hg concentrations high and worse neurotoxic symptoms when compared to non-miners from the same community